2004
DOI: 10.1177/1043454203262698
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment of Adolescent Siblings of Hematopoietic Stem Cell Transplant Patients

Abstract: Hematopoietic stem cell transplantation (HSCT) is a widely practiced therapy for many life-threatening childhood disorders. The authors investigated the psychosocial effects of HSCT on siblings of pediatric HSCT patients (n = 44; 21 donors, 23 nondonors, ages 6 to 18 years). Donor siblings reported significantly more anxiety and lower self-esteem than did nondonors. Nondonors showed significantly more school problems. Approximately one third of all siblings reported moderate to severe posttraumatic stress. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 19 publications
(27 reference statements)
4
62
3
Order By: Relevance
“…The literature has shown that siblings of HSCT patients are at risk of developing emotional reactions such as post-traumatic stress disorder, anxiety, and overall low self-esteem. [31][32][33][34] Pot-Mees and Zeitlin 8 found new behavior problems occurred far more frequently among siblings who were BM donors than among nondonors. See Table 4 for a list of psychosocial reactions specific to siblings.…”
Section: Psychosocial Effectmentioning
confidence: 99%
“…The literature has shown that siblings of HSCT patients are at risk of developing emotional reactions such as post-traumatic stress disorder, anxiety, and overall low self-esteem. [31][32][33][34] Pot-Mees and Zeitlin 8 found new behavior problems occurred far more frequently among siblings who were BM donors than among nondonors. See Table 4 for a list of psychosocial reactions specific to siblings.…”
Section: Psychosocial Effectmentioning
confidence: 99%
“…3032 Interestingly, rates of moderate-to-severe posttraumatic stress symptoms were equal among donor and nondonor siblings in 1 study. 31 In addition, siblings have indicated that their needs are not being met and have made suggestions about how the health care team could better support them. 13 …”
mentioning
confidence: 99%
“…10,11 But our data also document that the lack of choice was not a concern for either parents or children. Lack of choice, whether a concern or not, may imply the need for an advocate to help the family understand the medical options, but this information may be most effective coming from the treating physician.…”
Section: Discussionmentioning
confidence: 56%
“…5,6 One barrier to determining appropriate stringency for a donor protection policy is the relative lack of empirical data regarding the experience of families and specifically siblings who are typed and/or serve as donors. 7,8 Most studies have relied on cross-sectional, retrospective interviews years after donation, [9][10][11][12] with few exceptions. [13][14][15] Across these studies, both positive and negative psychosocial consequences of typing and donation are reported, including sibling donors' lack of choice, lack of appropriate information, and need for greater support.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
See 1 more Smart Citation